The Effect of Motivation and Human Resources Development on Employee Performance at Dukcapil Agency of Central Bengkulu Regency - Oni Susanti; Oni Yulianti; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
The purpose of the study was to determine the effect of motivation and Human Resource Development together on the performance of employees at the Dukcapil Agency of Central Bengkulu Regency. The sample in this study was 42 employees. The data collection method used a questionnaire and the analytical method used was Spearman rank correlation and hypothesis testing. Motivation has a strong influence on employee performance at the Dukcapil Agency of Central Bengkulu Regency with a correlation value of 0.754, it means that the higher the motivation, the higher the level of employee performance at the Dukcapil Agency. This result is strengthened by the results of hypothesis testing that tcount is greater than ttable (7.264 > 1.683). Thus the results of the hypothesis are H01 is rejected and Ha1 is accepted. This means that motivation has a significant influence on employee performance at Dukcapil Agency. HR development has a strong influence on employee performance with a correlation value of 0.662, it means that the higher the level of HR development, the higher the level of employee performance. These results are reinforced by the results of hypothesis testing that tcount is greater than ttable (5,585>1,683). Thus the results of the hypothesis are H02 is rejected and Ha2 is accepted. This means that the development of human resources has a significant influence on the performance of employees at the Dukcapil Agency of Central Bengkulu Regency.